FDG-PET/CT as a post-treatment restaging tool in urothelial carcinoma: Comparison with contrast-enhanced CT. Issue 3 (March 2016) - Kitajima, Kazuhiro; Yamamoto, Shingo; Fukushima, Kazuhito; Yamakado, Koichiro; Katsuura, Takayuki; Igarashi, Yoko; Kawanaka, Yusuke; Mouri, Miya; Hirota, Shozo
Abstract: Purpose: To assess the clinical usefulness of FDG-PET/CT in the diagnosis of recurrent and metastatic urothelial carcinoma in comparison with contrast-enhanced CT. Materials and methods: Eighty-three patients who had undergone treatment for histopathologically proven urothelial carcinoma underwent whole-body FDG-PET/CT and contrast-enhanced CT for suspected recurrence within a time interval of two weeks. Patient-based analysis and lesion sites besides the urinary tract, as interpreted by two experienced readers, were compared between the two modalities using McNemar test. Lesion status was determined on the basis of histopathology, radiological imaging and clinical follow-up for longer than 6 months. Result: Patient-based analysis showed that the sensitivity, specificity, and accuracy of FDG-PET/CT were 97.4%, 93.3% and 95.2%, respectively, whereas those of contrast-enhanced CT were 86.8%, 93.3% and 90.4%, respectively. The sensitivity and accuracy of FDG-PET/CT were higher than contrast-enhanced CT without significant difference ( p  = 0.13). The sensitivity of FDG-PET/CT for diagnosis of bone metastasis was significantly higher than that of contrast-enhanced CT (93.8% vs. 25%, p  = 0.0026). Conclusion: FDG-PET/CT is a more accurate modality than CT for assessment of recurrence outside the urinary tract in patients with urothelial carcinoma, especially for bone lesion. Cystoscopy, urine cytology, and FDG-PET/CT are complementary procedures and may have a definite management role.